ANTIBACTERIAL ACTIVITY OF SAMBILOTO (ANDROGRAPHIS PANICULATA, NEES) ETHANOL EXTRACT AGAINST STAPHYLOCOCCUS AUREUS - Naimah Putri; Latifah Listyalina (Politek ATK Yogyakarta Press, 2023)
The use of traditional plants can be used as natural antibacterial in preventing and treating infectious wound diseases caused by Staphylococcus aureus. One of the plants that can be used is bitter leaf. Sambiloto leaves contain several substances that can be used as antibacterial including alkaloids, flavonoids, saponins and tannins. The purpose of this study were to determine the lowest concentration of bitter leaf extract (Andrographis paniculata, Nees) which can inhibit and kill Staphylococcus aureus field isolates in vitro by dilution method. This research was expected to provide information on the benefits of bitter leaf as a drug that can be used in the treatment of infections against Staphylococcus aureus. This study used the dilution method which included Minimum Inhibitory Concentration (MIC) and Minimum Bacteriocid Concentration (MBC). The test results showed that bitter leaf extract (Andrographis paniculata, Nees) had the ability to inhibit the growth of Staphylococcus aureus starting at a concentration of 25% and had the ability to kill Staphylococcus aureus starting at a concentration of 50%.